Evaluation of the frequency of musculoskeletal disorders and work posture analysis by RULA method in workers of an auto- part manufacturing company - M Mostaghaci; MH Davari; F Mollaei; M Salehi; AH Mehrparvar (طب کار)
Intruduction: Musculoskeletal disorders are among the most common disorders due to ergonomic risk factors. This study was designed to evaluate the frequency of musculoskeletal disorders in an auto-part manufacturing company in 2010. Methods: This descriptive-analytic study was conducted on 94 welders and operators of an auto-part manufacturing company. The method of sampling was census. We used NMQ and RULA method for evaluation of MSDs and Work postures. Data was analyzed using SPSS (ver. 17). Results: Mean age of the subjects was 30.44 years (range: 20-56 years). The age group with the most frequent musculoskeletal disorders was 20-29 years (52.1%). Mean employment duration of the subjects was 5.2 years (range: 0-12 years). According to the results of NMQ, 70.2% of the subjects had experienced pain or discomfort in one of the areas of musculoskeletal system. According to RULA method 50.95% of subjects had RULA score=7 which takes place in action level 4. There was a statistically significant relationship between age and employment duration and musculoskeletal disorders (p<0.05). Conclusion: This study showed that musculoskeletal disorders were more frequent in low back. Considering that the action level of 4 was the most frequent one among the workers (50.9%), immediate ergonomic intervention is necessary.